Effect of hypothyroidism on contractile performance of isolated end-stage failing human myocardium. - Nancy S Saad; Mohammed A Mashali; Mohammad T Elnakish; Austin Hare; Courtney M Campbell; Salome A Kiduko; Kyra K Peczkowski; Amanda W Huang; Farbod Fazlollahi; Gina S Torres Matias; Amany A E Ahmed; Bryan A Whitson; et al. (PLoS ONE, 2022)
The relationship between hypothyroidism and the occurrence and progression of heart failure (HF) has had increased interest over the past years. The low T3 syndrome, a reduced T3 in the presence of normal thyroid stimulating hormone (TSH), and free T4 concentration, is a strong predictor of all-cause mortality in HF patients. Still, the impact of hypothyroidism on the contractile properties of failing human myocardium is unknown. Our study aimed to investigate that impact using ex-vivo assessment of force and kinetics of contraction/relaxation in left ventricular intact human myocardial muscle preparations. Trabeculae were dissected from non-failing (NF; n = 9), failing with no hypothyroidism (FNH; n = 9), and failing with hypothyroidism (FH; n = 9) hearts. Isolated muscle preparations were transferred into a custom-made setup where baseline conditions as well as the three main physiological modulators that regulate the contractile strength, length-dependent and frequency-dependent activation, as well as β-adrenergic stimulation, were assessed under near-physiological conditions. Hypothyroidism did not show any additional significant impact on the contractile properties different from the recognized alterations usually detected in such parameters in any end-stage failing heart without thyroid dysfunction. Clinical information for FH patients in our study revealed they were all receiving levothyroxine. Absence of any difference between failing hearts with or without hypothyroidism, may possibly be due to the profound effects of the advanced stage of heart failure that concealed any changes between the groups. Still, we cannot exclude the possibility of differences that may have been present at earlier stages. The effects of THs supplementation such as levothyroxine on contractile force and kinetic parameters of failing human myocardium require further investigation to explore its full potential in improving cardiovascular performance and cardiovascular outcomes of HF associated with hypothyroidism.